Disease site as a determinant of survival outcome in patients with systemic anaplastic lymphoma kinase positive anaplastic large cell lymphoma with extranodal involvement: an analysis of 1306 cases from the US National Cancer Database. (30th March 2018) - Nguyen, Kevin A.; Su, Chang; Bai, Harrison X.; Zhang, Zishu; Xiao, Rong; Karakousis, Giorgos; Zhang, Paul J.; Zhang, Guiying
Summary: Systemic anaplastic lymphoma kinase positive (ALK+) anaplastic large cell lymphoma with extranodal involvement (ALCL‐E) is a rare form of non‐Hodgkin lymphoma. No large study in the literature has compared the survival outcomes among different primary extranodal sites of involvement in ALK+ ALCL‐E. We identified 1306 patients with ALK+ ALCL‐E diagnosed between 2004 and 2014 in the US National Cancer Database, among whom 387 had primary extranodal site in the chest/abdomen/pelvis, 103 in the bone, 62 in the central nervous system, 134 in the head and neck and 620 in the cutaneous/soft tissue. Younger age, lower Charlson‐Deyo score, lower clinical stage, receipt of chemotherapy and receipt of radiotherapy were predictors of longer overall survival. Patients with extranodal involvement of central nervous system and chest/abdomen/pelvis had shorter overall survival than those with involvement of head and neck, bone, and cutaneous/subcutaneous tissue after adjusting for confounding variables. We recommend treating these patients upfront with more aggressive therapy.